EMPLOYEE PERFORMANCE IMPROVEMENT STRATEGY IN EFFORTS TO IMPROVE CUSTOMER RELATIONS USING HIERARCHY PROCESS ANALYSIS AND CUSTOMER RELATIONSHIP MANAGEMENT METHODS AT PT.MASAJI KARGOSENTRA TAMA BELAWAN - Muhammad Sadani; Prihatin Lumbanraja; Meilita Tryana Sembiring (RADJA PUBLIKA, 2023)
Based on the analysis and discussion of research regarding complaint handling at PT. Masaji Kargosentra Tama, it can be concluded as follows. Employee performance appraisal at PT Masaji Kargosentra Tama is carried out using a comprehensive approach. This performance appraisal process involves various KPI parameters related to customer service. For each KPI parameter, employees are given an assessment based on a predetermined scale or scoring system. This rating scale allows management to measure the quality of employee performance in aspects relevant to their duties and responsibilities. This assessment can be carried out periodically, for example every month or every year, using available data and information. During the assessment process, the management of PT Masaji Kargosentra Tama evaluates employee performance by considering each KPI parameter separately or as a whole. This performance appraisal can involve various methods, such as direct observation, data collection, interviews, or feedback from customers and colleagues. After getting the assessment results. Based on the results of the analysis using AHP, the division that has the highest assessment score is 3.15, followed by Operations with a score of 2.84, followed by Finance with a score of 2.01. So it is found that the commercial division is the focus in service to customers. With a strong focus on customer service, companies can direct efforts and resources to improve service quality, respond effectively to customer needs, and build good relationships with customers. Priority given to customer service will help companies to increase customer satisfaction, maintain customer loyalty, and achieve competitive advantage in a highly competitive industry. The proposed strategy that can be carried out by PT Masaji Kargosentra Tama is to create a customer membership system. The goal is for customers to get special services such as offering special prices, thereby increasing customer satisfaction. And for companies to find out detailed customer information so as to increase the possibility of carrying out customer programs as the implementation of a more personal customer relationship management (CRM) strategy.